PERFORMANCE OF FUNCTIONAL INSTRUCTOR OFFICIALS REVIEWED FROM MOTIVATION, COMPETENCE, DISCIPLINE AND INTERPERSONAL COMMUNICATION OF INSTRUCTORS OF VOCATIONAL TRAINING AND PRODUCTIVITY CENTER (BPVP) SURAKARTA - Mainulisma, Mainulisma (Program Studi Manajemen Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to analyze the influence of motivation, competence, discipline, and interpersonal communication on the performance of functional officers at the Vocational Training and Productivity Center (BPVP) Surakarta. The research involved all 130 functional instructor officers using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that motivation, competence, discipline, and interpersonal communication each have a positive and significant effect on the performance of functional officers. These findings indicate that improvements in these factors can enhance the performance of functional officers at BPVP Surakarta.